Utilization of Steel Slag in Agriculture (Review) - Rina Devnita; Apong Sandrawati; Mahfud Arifin (Fakultas Pertanian Universitas Padjadjaran, 2021)
The process of refining iron by Blast Furnace (BF) or Electric Arc Furnace (EAF) produces steel and by-product: steel slag. This by-product can be used for various fields such as construction, industry and agriculture. This paper aimed to discuss the use of steel slag in agriculture as fertilizer, lime and ameliorant in the soils. The content of elements and compounds in steel slag is the basic component for the utilization of this material, therefore they are displayed quite completely. The presence of other contents like of heavy metals which are classified as hazardous toxic materials is also stated. Utilization of steel slag for agriculture has been carried out widely in various countries such as Japan, Germany and the United States. There have been many studies of steel slag in Indonesia that prove the benefits of steel slag in adding nutrients and improving soil reactions. However, the use of this material is still limited to research field, has not been widely used. Meanwhile, many research has proven that steel slag can improve some chemical characteristics like pH and CEC, as well improve Ca, Mg and Si content. Steel slag can release P from retention and fixation and Andisols and Ultisols. Research showed that steel slag improved the yield of rice, maize, horticultural and industrial plants.